Globalization, trade imbalances, and labor market adjustment - Rafael Dix Carneiro; Jo\~ao Paulo Pessoa; Ricardo Reyes-Heroles; Sharon Traiberman (W.E. Upjohn Institute for Employment Research, 2021)
We study the role of global trade imbalances in shaping the adjustment dynamics in response to trade shocks. We build and estimate a general equilibrium, multicountry, multisector model of trade with two key ingredients: 1) consumption-saving decisions in each country commanded by representative households, leading to endogenous trade imbalances, and 2) labor market frictions across and within sectors, leading to unemployment dynamics and sluggish transitions to shocks. We use the estimated model to study the behavior of labor markets in response to globalization shocks, including shocks to technology, trade costs, and intertemporal preferences (savings gluts). We find that modeling trade imbalances changes both qualitatively and quantitatively the short- and long-run implications of globalization shocks for labor reallocation and unemployment dynamics. In a series of empirical applications, we study the labor market effects of shocks accrued to the global economy, their implications for the gains from trade, and we revisit the "China Shock" through the lens of our model. We show that the U.S. enjoys a 2.2 percent gain in response to globalization shocks. These gains would have been 73 percent larger in the absence of the global savings glut, but they would have been 40 percent smaller in a balanced-trade world.
Keywords: F16; 330; Globalization; Trade Imbalances; Labor Markets; Unemployment